Investigation of the High Energy Single Pulses Affect on Micro Arc Oxidation Process on Aluminium - Yılmaz, Mustafa Safa; Şahin, Orhan (Avestia Publishing, 2018)
Micro Arc Oxidation (MAO) was applied by using high anodic (500 volt) and high cathodic (500 volt) voltages with increasingly pulse duration couples (anodic and cathodic single pulses). While the increasing pulse duration, the single pulse energy was increased also. Due to the investigation of the single pulse affect, all other parameters were kept constant, such as duty cycle (8%), electrolyte temperature (25±5°C), electrolyte composition (KOH, Na2SiO3.5H2O), process time (20 minutes), anodic voltage, cathodic voltage and substrate. Five different anodic and cathodic pulse durations were applied. Scanning electron microscope (SEM), indenter, profilometer, eddy current, X-ray diffractometer were employed to investigate the microstructure, hardness, surface roughness, coating thickness and phase distribution of the coatings. The pore volume and distribution of the coating layers were analysed. Varying of pulse duration occurred significant differences among coating specifications. Coating layers with thickness between 50-90 μm and surface roughness between 3.1-5.2 μm were obtained. The hardness of coating layers was between 800-2000 Vickers. Coatings consist of two layers, inner dense layer and outer porous layer, which was a mixture of γ-Al2O3 and α-Al2O3. © 2019, Avestia Publishing.
Keywords: Aluminium; Coating; Micro arc oxidation; Surface characterization